2020
DOI: 10.3390/ijerph17134679
|View full text |Cite
|
Sign up to set email alerts
|

Be a Mom’s Efficacy in Enhancing Positive Mental Health among Postpartum Women Presenting Low Risk for Postpartum Depression: Results from a Pilot Randomized Trial

Abstract: In this study, we conducted a preliminary investigation of the efficacy of Be a Mom, a web-based self-guided intervention, in enhancing positive mental health among postpartum women at low risk for postpartum depression. Additionally, we examined Be a Mom’s efficacy regarding secondary outcomes as well as its acceptability and adherence. A total of 367 participants were randomly assigned to the Be a Mom group (n = 191) or to the waiting-list control group (n = 176) and completed baseline (T1) and posti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 77 publications
(95 reference statements)
1
40
0
Order By: Relevance
“…Five of the studies included in this Special Issue focused on the assessment of ICT tools for the prevention [ 3 , 4 ] and treatment [ 5 , 6 ] of mental disorders, or the promotion of mental health [ 7 ], in different populations. Specifically, these studies examined the interventions’ effectiveness, clinical utility, acceptability, or feasibility through pilot trials or randomized controlled trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the studies included in this Special Issue focused on the assessment of ICT tools for the prevention [ 3 , 4 ] and treatment [ 5 , 6 ] of mental disorders, or the promotion of mental health [ 7 ], in different populations. Specifically, these studies examined the interventions’ effectiveness, clinical utility, acceptability, or feasibility through pilot trials or randomized controlled trials.…”
mentioning
confidence: 99%
“…Moreover, the profile of patients who can benefit most from the intervention was analyzed. Monteiro et al [ 7 ] conducted one of the first trials examining the effectiveness, acceptability, and feasibility of a self-guided web-based intervention that was originally developed for preventing postpartum depression among high-risk women, in promoting positive mental health among women presenting low risk for postpartum depression, as even those women face significant challenges to their adjustment and may benefit from mental health promotion interventions. The results showed that women in the intervention group presented a larger increase in positive mental health compared to women in the waiting-list control group, with a large proportion of women showing good acceptability of the intervention.…”
mentioning
confidence: 99%
“…More specifically, positive emotions also appear to broaden one's thought-action repertoires and facilitate behavioral flexibility and build personal resources, such as social relationships and resilience (18)(19)(20). Considering these benefits and the call for prioritization of research focused on positive mental health (21), increasing studies have focused on directly addressing positive mental health as an intervention outcome [e.g., (22,23)], including in the perinatal period (10,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Although still limited and very recent, there is preliminary evidence of web-based cognitive behavioral therapy (CBT) interventions as well as compassionate and acceptance-based approaches in enhancing positive mental health in perinatal samples (10,24). This is the case of Be a Mom, a CBT unguided web-based intervention, which was recently found to be effective in improving positive mental health among low-risk postpartum women (25). Be a Mom incorporates aspects of third-wave CBT approaches and addresses concerns specific to the postpartum period [for the formative evaluation process that informed the design and intervention components see (47)].…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot exclude that they also have challenges and limitations, related with low digital literacy or with safety and privacy issues, among others [2].The present Special Issue focuses on acceptability, cost-effectiveness, potentialities, and limitations of ICT-based psychological services for mental health promotion, prevention, and treatment. Sixteen articles are included in this special issue from different international research teams working in China, Portugal, Spain, and the United States.Five of the studies included in this Special Issue focused on the assessment of ICT tools for the prevention [3,4] and treatment [5,6] of mental disorders, or the promotion of mental health [7], in different populations. Specifically, these studies examined the interventions' effectiveness, clinical utility, acceptability, or feasibility through pilot trials or randomized controlled trials.…”
mentioning
confidence: 99%